2014
DOI: 10.1212/wnl.0000000000000468
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Reasoning: A 72-year-old man with rapid cognitive decline and unilateral muscle jerks

Abstract: A 72-year-old man presented with cognitive decline and unilateral muscle jerks. Three months prior to presentation, the patient suddenly developed violent muscle jerks involving the right side of his body and face that impaired his gait and balance. Approximately 1 week later, he acutely developed confusion and memory loss. Over the following weeks, he experienced fluctuating symptoms of confusion, memory impairment, insomnia, and paranoid delusions. His muscle jerks and unstable gait were intermittent with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…In contrast, BG MRI abnormalities were exclusive to LGI1-Ab encephalopathy patients with FBDS and were typically contralateral to episodes (e.g., figure 2 ), suggesting a BG origin, which is consistent with the conclusions of prior publications on FBDS. 2 , 3 , 16 This is further supported by the characteristic semiology and the few previously reported cases of T2 hyperintensities, 2 , 3 , 17 , 18 FDG-PET hypermetabolism, 2 , 3 and T1 hyperintensity in the BG (only 2 other cases to our knowledge) 19 , 20 ; furthermore, LGI1 mutant mice develop dystonia. 13 Our study demonstrated that BG T1 hyperintensity can be reliably detected by neuroradiologists.…”
Section: Discussionsupporting
confidence: 81%
“…In contrast, BG MRI abnormalities were exclusive to LGI1-Ab encephalopathy patients with FBDS and were typically contralateral to episodes (e.g., figure 2 ), suggesting a BG origin, which is consistent with the conclusions of prior publications on FBDS. 2 , 3 , 16 This is further supported by the characteristic semiology and the few previously reported cases of T2 hyperintensities, 2 , 3 , 17 , 18 FDG-PET hypermetabolism, 2 , 3 and T1 hyperintensity in the BG (only 2 other cases to our knowledge) 19 , 20 ; furthermore, LGI1 mutant mice develop dystonia. 13 Our study demonstrated that BG T1 hyperintensity can be reliably detected by neuroradiologists.…”
Section: Discussionsupporting
confidence: 81%
“…tonic-dystonic or myoclonic-dystonic) is not unique to our patient and is reported in more than one-third of all the cases published in the literature ( Table 1 ). Of these mixed phenotypes, tonic-dystonic was the commonest phenotype [13] , [14] , [17] , [18] , [19] , followed by myoclonic-dystonic subtype [20] , [21] .…”
Section: Discussionmentioning
confidence: 99%
“…LGI-1 encephalitis is a rare neurological disorder with sub-acute course of progressive encephalopathy and FBDS [1,2] and which is the autoantigen associated with limbic encephalitis previously attributed to voltagegated potassium channels [3] . In addition to clinical manifestation of classic limbic encephalitis, some patients may develop hyponatremia and have preceding or concomitant myoclonic-like jerks described as FBDS [4,5] . and its incidence is rising.…”
Section: Introductionmentioning
confidence: 99%